2022
DOI: 10.1002/adma.202108637
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Skyrmions in a Thickness Tunable 2D Ferromagnet from a Defect Driven Dzyaloshinskii–Moriya Interaction

Abstract: There is considerable interest in van der Waals (vdW) materials as potential hosts for chiral skyrmionic spin textures. Of particular interest is the ferromagnetic, metallic compound Fe3GeTe2 (FGT), which has a comparatively high Curie temperature (150–220 K). Several recent studies have reported the observation of chiral Néel skyrmions in this compound, which is inconsistent with its presumed centrosymmetric structure. Here the observation of Néel type skyrmions in single crystals of FGT via Lorentz transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 53 publications
(86 reference statements)
6
54
0
Order By: Relevance
“…With this in mind, we tentatively suggest that in such thick samples, any present interfacial DMI from the oxide layer may no longer be sufficient to stabilise Néel-type domain walls, and this would provide strong indication that the DMI observed in FGT flakes must be due to some interfacial effect. However, recent studies have suggested that the DMI could instead be due to some intrinsic property of the bulk material, either due to vacancy driven DMI 38 or additional higher order effects 39 . Further work may be required to elucidate the true origin of the monochrial Néel-type domain walls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With this in mind, we tentatively suggest that in such thick samples, any present interfacial DMI from the oxide layer may no longer be sufficient to stabilise Néel-type domain walls, and this would provide strong indication that the DMI observed in FGT flakes must be due to some interfacial effect. However, recent studies have suggested that the DMI could instead be due to some intrinsic property of the bulk material, either due to vacancy driven DMI 38 or additional higher order effects 39 . Further work may be required to elucidate the true origin of the monochrial Néel-type domain walls.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the formation of magnetic skyrmions—topological nanoscale whirls in the spin structure of magnetic materials 30 , 31 —has been reported in FGT flakes 32 38 . This discovery opens up further prospective applications such as 2D skyrmion racetrack or neuromorphic computing devices 40 , 41 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some instances, if multiple pairs of layers have displaced in different ways, the inversion symmetry could be broken in this fashion. Moreover, a recent experimental work reports a discrepancy in the occupancy of the central Fe atom in the A layer versus the B layer [49]. This implies that the unit cell is no longer inversion symmetric, providing the avenue required for bulk torque generation.…”
Section: Somentioning
confidence: 99%
“…by surfaces and interfaces [14,15], inversion sym-metry present in ideal bulk FGT ultimately suppresses the overall torque on the magnetization. However, the reality is that there are a variety of "intrinsic" mechanisms which can drive the inversion symmetry breaking in this bulk system [15,49]. One of these effects is that of magnetostriction [50].…”
Section: Somentioning
confidence: 99%